Molnupiravir and Nirmatrelvir/Ritonavir: The New Available Antiviral Options for COVID-19 - Samuel Theodorus Sutanto; Robert Sinto; Adeline Pasaribu; Sharifah Shakinah (Interna Publishing, 2022)
Coronavirus disease 2019 (COVID-19) is a respiratory tract disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). With the complexity of multimorbidity in Indonesia, it is crucial to find another line of antiviral for COVID-19. This article aims to review two antivirals, molnupiravir and nirmatrelvir/ritonavir, that have been studied extensively in treating COVID-19 with promising results, and their availability in Indonesia. Molnupiravir and nirmatrelvir/ritonavir are two of many repurposed drugs in clinical trials, which have been reported to have a mechanism in quick clearance of SARS-CoV-2, reduction in viral load, and fast symptoms recovery time in phase 1 and 2 clinical trials. Phase 2/3 clinical study in COVID-19 patients without any indication for hospitalization showed that molnupiravir and nirmatrelvir/ritonavir significantly reduced the risk of hospitalization and death.